1987
DOI: 10.1073/pnas.84.20.7198
|View full text |Cite
|
Sign up to set email alerts
|

DNA inversion within the apolipoproteins AI/CIII/AIV-encoding gene cluster of certain patients with premature atherosclerosis.

Abstract: The genes coding for apolipoproteins (apo) AI, CIII, and AIV, designated APOA1, APOC3, and APOA4, respectively, are closely linked and tandemly organized in the long arm of the human chromosome 11. A DNA rearrangement involving the genes encoding apoAI and apoCIHl in certain patients with premature atherosclerosis has been associated with deficiency of both apoAI and apoCIll in the plasma of these patients. Structural characterization of the genes for apoAI and apoCIII in one of these patients indicates that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(38 citation statements)
references
References 34 publications
(34 reference statements)
0
35
2
Order By: Relevance
“…In humans an inverse correlation between the risk of developing atherosclerosis and plasma levels of HDL has been observed (12). Human individuals deficient in apoA-I caused by several different types of mutation in the gene appear to be predisposed to atherosclerosis (13)(14)(15)(16)(17)(18). These observations point to the importance of apoA-I and HDL particles in atherogene-SIS.…”
mentioning
confidence: 69%
“…In humans an inverse correlation between the risk of developing atherosclerosis and plasma levels of HDL has been observed (12). Human individuals deficient in apoA-I caused by several different types of mutation in the gene appear to be predisposed to atherosclerosis (13)(14)(15)(16)(17)(18). These observations point to the importance of apoA-I and HDL particles in atherogene-SIS.…”
mentioning
confidence: 69%
“…1,2,30 Subjects at highest risk include those with apoA-I/C-III/A-IV deficiency, 7,8 reduced apoA-I synthesis, 9 or the presence of additional cardiovascular risk factors. 12,13 There are several mechanisms whereby HDL-C deficiency may enhance CAD risk.…”
Section: Discussionmentioning
confidence: 99%
“…These cases have ranged from single point mutations in the apoA-I gene to large deletions or chromosomal aberrations in the apoA-I/C-III/ A-IV gene complex. [7][8][9][10] However, HDL-C deficiency states resulting from structural apoA-I changes do not inevitably result in premature CAD. 11 Recently, severe HDL-C deficiency was associated with premature CAD only when accompanied by additional CAD risk factors.…”
mentioning
confidence: 99%
“…In certain patients with premature coronar} ~ artery disease, it has been shown that di.~ruptioa of' the structure of this gone cluster results in altered expression of the apo A-I and apo CIII genes leading to combined apo A-I, apo CIII and HDL deficiency, the major risk factor for accelerated atheroselerosis in these patients [10].…”
Section: Introductionmentioning
confidence: 99%